A Practical and Efficient Stereoselective Synthesis of (S)‐Rivastigmine and (R)‐Rivastigmine. Issue 5 (2nd February 2018) - Hua, Yong‐Gang; Han, Lan‐Ping; Yang, Qian‐Qian; Wang, Mei‐Jing; Zhang, En; Liu, Hong‐Min
Abstract: A stereoselective synthesis of (S)‐rivastigmine and (R)‐rivastigmine was developed. The key steps were stereoselective chlorination of a chiral secondary benzylic alcohol intermediate and amination of the corresponding chloride. Based on this method, both stereoisomers of rivastigmine were obtained stereoselectively in high yields. Abstract : A new methods for stereoselective synthesis of rivastigmine has been developed. This strategy avoids the chiral intermediates waste produced by the traditional lipase‐catalyzed strategy. The key steps provide chlorination of a chiral secondary benzylic alcohol conditions.